Transient Developmental Purkinje Cell Axonal Torpedoes in Healthy and Ataxic Mouse Cerebellum - Ljungberg, Lovisa; Lang-Ouellette, Daneck; Yang, Angela; Jayabal, Sriram; Quilez, Sabrina; Watt, Alanna J. (Frontiers in Cellular Neuroscience, 2016)
Information is carried out of the cerebellar cortical microcircuit via action potentials propagated along Purkinje cell axons. In several human neurodegenerative diseases, focal axonal swellings on Purkinje cells – known as torpedoes – have been associated with Purkinje cell loss. Interestingly, torpedoes are also reported to appear transiently during development in rat cerebellum. The function of Purkinje cell axonal torpedoes in health as well as in disease is poorly understood. We investigated the properties of developmental torpedoes in the postnatal mouse cerebellum of wildtype and transgenic mice. We found that Purkinje cell axonal torpedoes transiently appeared on axons of Purkinje neurons, with the largest number of torpedoes observed at postnatal day 11 (P11). This was after peak developmental apoptosis had occurred, when Purkinje cell counts in a lobule were static, suggesting that most developmental torpedoes appear on axons of neurons that persist into adulthood. We found that developmental torpedoes were not associated with a presynaptic GABAergic marker, indicating that they are not synapses. They were seldom found at axonal collateral branch points, and lacked microglia enrichment, suggesting that they are unlikely to be involved in axonal refinement. Interestingly, we found several differences between developmental torpedoes and disease-related torpedoes: developmental torpedoes occured largely on myelinated axons, and were not associated with changes in basket cell innervation on their parent soma. Disease-related torpedoes are typically reported to contain neurofilament; while the majority of developmental torpedoes did as well, a fraction of smaller developmental torpedoes did not. These differences indicate that developmental torpedoes may not be functionally identical to disease-related torpedoes. To study this further, we used a mouse model of spinocerebellar ataxia type 6 (SCA6), and found elevated disease-related torpedo number at two years. However, we found normal levels of developmental torpedoes in these mice. Our findings suggest that the transient emergence of Purkinje cell axonal torpedoes during the second postnatal week in mice represents a normal morphological feature in the developing cerebellar microcircuit.